2011
DOI: 10.1111/j.1365-2052.2010.02081.x
|View full text |Cite
|
Sign up to set email alerts
|

Identification and genetic effect of haplotypes in the promoter region of porcine myostatin gene

Abstract: Myostatin plays a pivotal role in controlling skeletal muscle mass in mammals. Polymorphisms in its promoter region likely impact on transcription and production traits. In this study, haplotypes involving three polymorphic sites in the promoter region of the porcine myostatin gene, namely at sites 435, 447 and 879, were identified and their effect on production traits, gene expression as well as on skeletal muscle traits were analysed. Four haplotypes were revealed and the linkage disequilibrium and evolution… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 28 publications
0
13
0
1
Order By: Relevance
“…; Liu et al . ) demonstrated that these two SNPs in Duroc, Yorkshire, Landrace were in linkage disequilibrium (p < 0.05) as measured by chi‐squared tests. Our previous results shown that MSTN 435AA/447AG, 435GA/447AA and 435AA/447AA appeared in Duroc (Tu et al .…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…; Liu et al . ) demonstrated that these two SNPs in Duroc, Yorkshire, Landrace were in linkage disequilibrium (p < 0.05) as measured by chi‐squared tests. Our previous results shown that MSTN 435AA/447AG, 435GA/447AA and 435AA/447AA appeared in Duroc (Tu et al .…”
Section: Resultsmentioning
confidence: 97%
“…; Liu et al . ); Chinese Meishan pigs have no linkage disequilibrium in these two SNPs. Meishan pigs were all fixed as AA homozygotes for both the MSTN g.435G>A and g.447A>G mutations (Tu et al .…”
Section: Discussionmentioning
confidence: 93%
“…Stinckens et al [24] reported a very high allele frequency of A447G in the Pietrain pig breed, for the SNP located at site 447 (A447G); while SNPs G435A and T879A were found to be associated with early growth traits in Duroc pigs and strong linkage disequilibrium exists between them [24]. Liu et al [34] analysed the associations of this haplotype with birth weight and early growth. A favourable effect on body weight was found for the allele carrying G 435 -A 447 -T 879 [34].…”
Section: Resultsmentioning
confidence: 99%
“…Liu et al [34] analysed the associations of this haplotype with birth weight and early growth. A favourable effect on body weight was found for the allele carrying G 435 -A 447 -T 879 [34]. The expression of porcine myostatin gene was investigated by qRT-PCR [25,26] and by functional activity of reporter gene [34].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation